Extended Games Played by Managerial Firms - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
The issue of timing is addressed in a game between managerial firms. The choice over timing can be taken either by managers or by entrepreneurs. It is shown that (i) delegation drastically modifies the owners' preferences concerning the distribution of roles, as compared to the setting where firms act as pure profitmaximizers; and (ii) the ability of moving first in the market game entails that, at least observationally, the owner of the leading firm prefers not to delegate. I show that the choice of the timing by managers entails the same profit owners would achieve by specifying the timing in the delegation contract.
Keywords: 330